2001
DOI: 10.1007/s002530000479
|View full text |Cite
|
Sign up to set email alerts
|

Expression level of heterologous proteins in Pichia pastoris is influenced by flask design

Abstract: The yeast Pichia pastoris is a convenient production system that enables expression of heterologous proteins in high amounts. As a fermentation method, shaking flasks are very popular because of their simplicity of handling and their low cost. We compared the expression level of the enzyme acetylcholinesterase in a transformed strain of P. pastoris grown in different flasks, presenting various designs but all with the same volume. A several-thousand-fold difference appeared in the expression levels; and the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 11 publications
3
24
0
Order By: Relevance
“…Production of large amounts of heterologous proteins in shake-flask culture is difficult, due to the limitations of volume, oxygen transfer, substrate addition and an inability to monitor these factors efficiently. Methods of monitoring methanol in shake flasks are available, such as organic solvent vapour detectors [40], and the oxygen transfer of these systems can be increased by the use of baffles [114]. On-line measurement of oxygen and carbon dioxide transfer rates in shake flasks has also been demonstrated using a respiration activity monitoring system (RAMOS) [100].…”
Section: Production Of Heterologous Proteins In P Pastorismentioning
confidence: 99%
“…Production of large amounts of heterologous proteins in shake-flask culture is difficult, due to the limitations of volume, oxygen transfer, substrate addition and an inability to monitor these factors efficiently. Methods of monitoring methanol in shake flasks are available, such as organic solvent vapour detectors [40], and the oxygen transfer of these systems can be increased by the use of baffles [114]. On-line measurement of oxygen and carbon dioxide transfer rates in shake flasks has also been demonstrated using a respiration activity monitoring system (RAMOS) [100].…”
Section: Production Of Heterologous Proteins In P Pastorismentioning
confidence: 99%
“…With P. pastoris systems, it has been shown that this increase in expression is strongly dependent on the extent of aeration and the shape of the baffles used. 58 Interestingly, it has been observed that dramatic differences in the expression levels of acetylcholinesterase occur with flasks with different shaped baffles, but these expression levels do not correlate with oxygenation levels in these flasks, suggesting the other factors besides oxygenation influence expression levels in shakeflask cultures. 58 As anticipated, the addition of half concentrations of methanol for every 12 h gave enhanced levels of expression of activin A.…”
Section: Larger Scale Expression Studiesmentioning
confidence: 98%
“…Although it has been reported that P. pastoris represents an appropriate host for the expression of recombinant proteins, the low level of expression in this host could be attributed to several factors. These potential impediments include, the lack of consistency of codon usage of the bovine and pichia (8), copy number of the gene (9), the efficiency and strength of promoters (10), efficiency of translation signals (11) and signal peptides (12), processing and folding in the endoplasmic reticulum and Golgi apparatus (13), environmental factors of expression (14), extracellular secretion (15), and protein turnover by proteolysis (16,17). As the recombinant, colony number 6 is high geneticin resistant (which grown on 2 mg/mL of this Antibiotic), the copy number of the gene was not restrictive for recombinant protein production.…”
Section: Discussionmentioning
confidence: 99%